Robust Localization Algorithm Based on the RSSI Ranging Scope - Yan Huang; Jianying Zheng; Yang Xiao; Miao Peng (International Journal of Distributed Sensor Networks)
Wireless signal can be easily influenced by the environment in the propagation process. The signal propagation model is the most appropriate model for current indoor environment to ensure the ranging accuracy based on received signal strength indicator (RSSI). In this paper, we propose a robust localization algorithm based on the RSSI ranging scope by which the RSSI ranging error caused by using a fixed parameter in signal propagation model is dramatically eliminated. Our contributions in this paper are twofold. First, the influence of RSSI ranging error on positioning accuracy is well discussed in detail in the scope of the wireless signal propagation model. Second, we develop a robust localization algorithm which creates a one-to-one mapping between the RSSI value and the distance scope based on the value scope of path loss exponent in the signal propagation model. Simulation results indicate that the proposed localization algorithm based on the RSSI ranging scope is robust under different environments, when the real path loss exponent is difficult to measure accurately.